Revisiting justice in the first four Beatitudes in Matthew (5:3-6) and the story of the Canaanite woman (Mt 15:21-28): A postcolonial reading - Rukundwa, Lazare S. (HTS teologiese studies, 2005)
Reading the Gospel of Matthew from the perspective of postcolonial theory means taking the context of the Gospel seriously. The political and religious circumstances of Palestine under Roman colonization influenced Matthean redaction. From a this perspective, it can be argued that Matthew presents Jesus as a revolutionary leader whose divine mission was to challenge and overthrow the Roman empire and its local collaborators on behalf of the poor, the powerless, the afflicted, the hungry and the outcasts. His mission was to replace existing power structures with the universal, just and powerful kingdom of heaven on earth. The article argues that the story of the Canaanite woman (Mt 15:21-28) falls into this reality. She negotiates justice and righteousness on behalf of her demon-possessed daughter. Seen from the perspective of Jesus’ Beatitudes in Matthew (5:3-6), her encounter with Jesus helps him discover the wider scope of his healing mission, beyond geopolitical and cultural boundaries.